Effects of Winter Foliar Fertilizing and Plant Growth Promoters on Element and Carbohydrate Contents on the Shoot of Navel Orange Sapling. Issue 4 (1st October 2020) - Hasan, Ahmed Mohammad; Mohamed Ali, Tahani J.; Al-Taey, Duraid K.A.
ABSTRACT: The main aims of this paper are to evaluate the effects of winter foliar fertilizer and plant growth promoters on element and carbohydrate contents of the shoot of the navel orange sapling. This study was conducted in the lath house in the Agriculture College in Al-Qasim Green University during the period from 11-1-2014 to 6-1-2015. A factorial experiment (2 × 7) was done within a randomized complete block design with four replications. The first factor represented two foliar application dates of PRO-SOL fertilizer (1 g/L) every 2 weeks during winter–spring season (S1) in 2014–2015 and spring season dates (S2) in 2015). Second factor was foliar application of plant growth promoters in mid-March with indole butyric acid (IBA), 40 and 80 mg/L; forchlorfenuron (CPPU, KT-30), 15 and 30 mg/L; IBA+KT-30 (CPPU), 40 + 15 mg/L consecutively; and IBA+KT-30 (CPPU) 80 + 30 mg/L consecutively. The main effects due to the foliar fertilizing dates (S) were found to be highly significant for nitrogen content (%). While the second main factor plant growth promoter (T) was found to be highly significant for nitrogen and potassium content % and S × T interaction which were found to be significantly different for nitrogen, potassium and ferric content (%), respectively. Foliar fertilizing dates (S) caused a significant increase in nitrogen content (%). The experiment results showed that there different responses with treatments, the S2 with T7 treatment achieved the highest value value with ferric contents % while the same treatments recorded the lowest value in potassium contents %. Therefore, it was concluded from the results of the experiment that potassium uptake percent for in S2 not effective as well as T7: IBA at 80 ppm+ CPPU at 30 ppm.